Model for simulating scorpion substrate vibration and detection system - B.A, sadiq; Aibinu, Abiodun Musa; Joseph, E; Salau, H B; Salami, Momoh Jimoh Eyiomika (IOP Publishing, 2013)
Scorpion stings are vital health issues which requires prompt attention to minimize the pain inflicted on victims and avert death. A possible solution in averting the sting is the capability of detecting its presence earlier before it stings. Scorpion like other arthropods have a specific kind of movement pattern called substrate vibration, which generates a specific signal that is used in recognizing and locating mates and preys. This paper aims at developing an intelligent scorpion detection system using vibration frequency detection technique. A six step model for simulating scorpion substrate vibration and detection has been proposed. The surrounding vibrating signal is acquired and passed through a band pass filter. The resulting signal is model using autoregressive modeling technique. Resulting co-efficients are further analyzed for activity detection. The frequency response of scorpion activities for mating behaviour was simulated, detected analysed using MATLAB environment. The resulting coefficients was also compared and analysed. Results obtained shows that the proposed technique is appropriate for model and simulating scorpion substrate vibration and detection system.